Analisis Manajemen Risiko Keselamatan dan Kesehatan Kerja di PT Traya Tirta Kota Makassar - Susi Susanti; Suharni Suharni; Arman Arman (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2026)
Occupational safety and health are critical aspects in ensuring the smooth operation of drinking water treatment companies, as workers are exposed to potential physical, chemical, mechanical, electrical, and ergonomic hazards. The implementation of the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method is necessary for systematically managing workplace risks. This study aims to analyze the implementation of HIRARC at PT. Traya Tirta Makassar. The research design is qualitative with a descriptive approach. This study was conducted from September to October 2025 at PT. Traya Tirta Makassar. Informants were selected using purposive sampling, consisting of primary informants, key informants, and supporting informants. Data collection was conducted through field observations, in-depth interviews, documentation, and risk assessment using the HIRARC matrix based on the multiplication of probability and severity. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the company has routinely conducted hazard identification across five operational divisions: production, laboratory, HRD, mechanics, and workshop. The dominant risks identified include chemical exposure, slippery floors, noise, machine-related injuries, fire, and electric shock. The total identified risk levels consist of 8 high-risk categories, 14 medium-risk categories, and 11 low-risk categories. Risk controls have been implemented through the provision of PPE, technical engineering, safe work procedures, OSH training, routine inspections, and SMK3-based evaluations. The main constraint still identified is workers’ inconsistency in adhering to safety procedures. This study concludes that the implementation of HIRARC at PT. Traya Tirta Makassar is quite effective; however, improvements in safety culture and work discipline are needed to make risk controls more effective.